2016 IEEE Transportation Electrification Conference and Expo (ITEC) 2016
DOI: 10.1109/itec.2016.7520273
|View full text |Cite
|
Sign up to set email alerts
|

Economic and CO2 Emission Benefits of a Solar Powered Electric Vehicle Charging Station for Workplaces in the Netherlands

Abstract: The paper analyses the economic and environmental benefits of charging electric vehicles (EV) at workplaces in the Netherlands using photovoltaic panels (PV). A 10kW EV-PV charging system is used to charge the electric cars directly from photovoltaic panels. The cost of using a gasoline vehicle is compared with that of an electric vehicle that is charged from the grid or from solar panels. It is found that charging EV from PV results in huge savings in fuel cost, taxes and lower CO2 emissions. A comparison is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Indeed, high FITs incentivize PV capacity owners to sell their whole production to the grid instead of cooperating with an EV fleet, that have to charge only using the grid. [113] shows that low FIT make profitable investments on both PV and EV compared to PV and classical vehicles.…”
Section: Support Mechanismsmentioning
confidence: 99%
“…Indeed, high FITs incentivize PV capacity owners to sell their whole production to the grid instead of cooperating with an EV fleet, that have to charge only using the grid. [113] shows that low FIT make profitable investments on both PV and EV compared to PV and classical vehicles.…”
Section: Support Mechanismsmentioning
confidence: 99%
“…Using solar energy to power the charging stations of EVs, their CO 2 emissions will be reduced to 32 g CO 2 /kWh. Mouli et al (2016) showed that in The Netherlands, there would be a reduction in CO 2 emissions from 109 g/km to 70.5 g/km by replacing gasoline vehicles with EVs [65].…”
Section: Solar Energy In Transportationmentioning
confidence: 99%
“…Reduced energy demand on the grid as the EV charging power is locally generated from PV [31] 4. Reduced cost of EV charging and reduced impact of changes in PV feed-in tariffs [8] A. AC charging of EV from PV The charging of EV from PV can be done by using a conventional PV inverter and an EV charger which are both connected to the AC grid, as shown in Fig. 4.…”
Section: Solar Charging Of Evsmentioning
confidence: 99%
“…This makes EVs not truly green as one would expect. Hence it is important for the future that EVs are charged from sustainable sources of electricity like solar or wind [5]- [8]. At the same time, EV can play a decisive role with their ability to act as controllable load and as a storage for the grid with fast response.…”
Section: Introductionmentioning
confidence: 99%